Comparison of quality of life and improvement in B.P and blood glucose values of patients using branded generic and generic medicines for hypertensive and diabetes treatment - T, Vedavathi; N, Sadagam; RK, Ayyagari; RatnaJ, Vijaya (Indian Journal of Pharmacy Practice)
In India most of the drugs are generics only. But these drugs are supplied with the respective company's brand names and are thus termed as branded generics. There is no practical difference between branded generics and generics. But a difference exists at the marketing level where the generics are obtained by the retailer at a lower “price to the retailer” and there could be a difference in the way healthcare professionals perceive branded generics and generics. This work consists of a comparison of therapeutic efficacy of branded generics and generics of drugs used by B.P patients and patients having B.P and diabetes by comparing their health related quality of life (HRQOL) levels and their B.P levels and blood glucose levels, before and after treatment. The hypothesis behind the work is that if there is a significant difference between the therapeutic efficacy of branded generics and generics then there should be a significant difference between the HRQOL levels and improvements in B.P levels and blood glucose levels of the patients who are using them over a long period. This work is a study of HRQOL levels as determined by SF-36 questionnaire and B.P levels and blood glucose levels as ascertained from the case sheets of patients. Statistical analysis revealed that there is no significant difference between the branded generics and generics with respect to HRQOL values or reduction in the percentage of patients from high B.P levels to low B.P levels and from high blood glucose levels to low blood glucose levels. It was concluded that there is no difference between the therapeutic efficacy of branded generic drugs and generic drugs. It is suggested that the Drugs and Cosmetics Act 1940 be amended to differentiate between generic and branded generic products and to make it compulsory for the companies to keep a lower maximum retail price (MRP) on the labels of the generic products.
Keywords: HRQOL; SF-36; hypertension (B.P.); hypertension and diabetes; Branded generics (BG); Generics (G); Maximum retail price (MRP)